SERTIFIKASI PRODUK HALAL: DALAM PERSPEKTIF SOSIOLOGI HUKUM - Sopiah, Evi (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
In general, the physical needs of humans are very much. Among the many human needs, the human needs which fit into primary needs category is food as a basic human need for survival. Human can survive and thrive because they are sustained by the food consumed by them. Without consuming the food, the human body becomes weak. They cannot work, think or move. It is the laws (sunnatullah). This need to be considered by humans in feed or food, that fulfillment of the rules of law, especially regarding aspects of halal and haram. Embodiments of the need for halal products that it gives birth LPPOM by Indonesia Scholar Coulcil (MUI), so that the results of the agency comes a sense of assuredness of Muslims on a wide range of halal products which are symbolic inclusion of halal logo on the food product.